Epitope Spreading: The Underlying Mechanism for Combined Membranous Lupus Nephritis and Anti-GBM Disease? - Olusola Sogbein; Tina Kochar; Marjan Afrouzian (Case Reports in Nephrology)
Membranous lupus nephritis associated with anti-GBM antibodies is a rare entity, particularly in lupus nephritis patients who are serologically negative for ANA and anti-dsDNA with normal complement levels. We present an unusual case of a patient initially diagnosed with anti-GBM disease whose repeat biopsy demonstrated combined focal proliferative and membranous lupus nephritis (III + V). The first biopsy showed a granular linear pattern, and the second biopsy had multiple electron dense deposits in the subendothelial, epithelial, and mesangial regions along with podocyte effacement. Experimental research suggests that the sequential histopathological transition observed may reflect the action of immunological rearrangement and epitope spreading.